The relative valuation of gold - Dirk G. Baur; Joscha Beckmann; Robert Czudaj (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2016)
Gold is a globally traded asset and held in large quantities by investors and central banks. Since there is no established model to assess if the price of gold is overvalued or undervalued, we propose a relative valuation framework based on gold price ratios. We analyze gold prices relative to commodity prices, consumer prices, stock prices, dividend and bond yields and find that the relative value of gold varies significantly over time indicating pronounced periods of mispricing of gold relative to other assets. An analysis of the factors which drive these variations demonstrates that inflation expectations and uncertainty have a strong influence on gold ratios while macroeconomic fundamentals are less important. More specifically, a boost in confidence decreases the relative price of gold while heightened uncertainty increases the relative price of gold which confirms the role of gold as a safe haven. – – Gold ist ein global gehandeltes Asset und wird in großen Mengen von Investoren und Zentralbanken gehalten. Da in der Literatur kein etabliertes Modell existiert, um zu beurteilen, ob der Goldpreis über- oder unterbewertet ist, schlagen wir eine relative Bewertung basierend auf Goldpreisrelationen vor. Wir analysieren den Goldpreis in Relation zu Rohstoffpreisen, Konsumentenpreisen, Aktienkursen, Dividenden und Renditen. Die Ergebnisse zeigen, dass der relative Wert des Goldes über die Zeit signifikant variiert. Es lassen sich Phasen identifizieren, die durch eine Fehlbewertung von Gold relativ zu anderen Vermögenswerten gekennzeichnet sind. Eine Analyse der Faktoren, die diese Schwankungen hervorrufen, weist Inflationserwartungen und Unsicherheit als entscheidende Determinanten von Fluktuationen in Goldrelationen aus, während makroökonomische Fundamentaldaten weniger relevant erscheinen. Ein Anstieg der Inflationserwartungen führt zu einem Rückgang des relativen Goldpreises, während eine Erhöhung der Unsicherheit den relativen Goldpreis ansteigen lässt, was die Rolle von Gold als "sicheren Hafen'" bestätigt.
Keywords: G10; G15; 330; Gold; relative valuation; gold-silver ratio; safe haven; Bayesian econometrics